Empowering Design through Flexible Personal Space - Alex Knezo (Oz, 2016)
An architecture focused on the specific interaction between users and their spaces, while employing a cohesive system of design paired with innovative technology, can personalize the design of architectural spaces. The customizable nature of systems allows the future of architecture to be linked to well-designed spaces that are tailored to the needs, wants, and attainability of almost anyone in the world. Current forces driving architectural and spatial design often fail to bring new and exciting design at a personal level to the majority of users. These forces focus on a large, detached element to satisfy the masses instead of focusing a design on how a single person uses a space. Designing for, and giving power to, individual users is the future of design, something many designers ignore in favor of extravagant forms, progressing technologies, or lowering costs, although none are mutually exclusive.